Community Screening for Preschool Child Inhibition to Offer the 'Cool Little Kids' Anxiety Prevention Programme. Issue 6 (18th March 2014) - Beatson, Ruth M.; Bayer, Jordana K.; Perry, Alexandra; Mathers, Megan; Hiscock, Harriet; Wake, Melissa; Beesley, Kate; Rapee, Ronald M.
<x xml:space="preserve">Abstract</x> Temperamental inhibition has been identified as a key risk factor for childhood anxiety and internalizing problems. An efficacious early prevention programme for shy/inhibited children has been developed; however, accurate, efficient and acceptable screening is needed to support wider implementation. We explore community screening options in the context of a trial implementing the Cool Little Kids prevention programme for anxiety disorders. In comparison to the Australian Temperament Project's inhibition scale, we examine the Strengths and Difficulties Questionnaire's (SDQ) ability to screen for inhibited preschool children. Parents of 6307 children aged 3 to 6 years enrolled in preschool programmes from eight socio‐economically diverse districts in Melbourne, Australia, first completed the measures of inhibition and SDQ. Parents with inhibited children then enrolled in the Cool Little Kids randomized trial (n = 545). Of these, 88% provided feedback about inhibition screening. Parents allocated to the intervention also provided feedback on the Cool Little Kids parenting programme. Results demonstrated that parents of preschool children (i) find inhibition screening acceptable, (ii) take up this parenting programme and (iii) report favourable feedback. The SDQ emotional symptoms subscale demonstrated acceptable sensitivity but insufficient specificity to identify inhibited preschool children. Presenting parents with a brief, validated inhibition scale could be a low‐cost option for identifying inhibited preschool children in the community to offer early anxiety prevention. Copyright © 2014 John Wiley & Sons, Ltd.